GRADATION AND GEOCHEMISTRY OF THE FENCED LAGOON SEDIMENTS (BANDAR ANZALI) WITH REGARD TOWARDS SOURCE ROCK AND TECTONIC LOCATION - Moghadam, Behnaz Rafiei; Rezaei, Khalil; Solgi, Ali; Ghiahchi, Pantea; AleAli, Mohsen (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The location of the Fenced Lagoon in the urban basin of Bandar Anzali, which should be considered due to its impact on the lives of the people of the region in terms of the conservation of the wetland and its environmental issues, and, on the other hand, the potential of this area to be introduced as a geotourism center determine the need to investigate the area's sedimentology and geochemistry. Therefore, to study sedimentary and geochemical properties of the Fenced Lagoon sediments located in Bandar Anzali, 33 samples were taken in the form of 6 cores and 12 grabs, andbasic sedimentation tests and heavy metals measurement were carried out through XRF. Studies show that the sediments are ranged from sand to clay in terms of gradation and have mainly costal-river origin. The sediments of this lake are classified into four sedimentary types: Muddy Sand, Slightly Gravely Muddy Sand, Sand and Slightly Gravely Sand and sand is the main component of all of these sediments. The most abundant sedimentary types belong to Muddy Sand and Sand and the least abundant sedimentary types belong to Slightly Gravely Muddy Sand and Slightly Gravely Sand. The nature of the source rock is derived from acidic to intermediate combination and in general, sedimentary rocks of the area under study are within the continental arch islands and, to a lesser extent, the active continental margin.
Keywords: Anzali port; sediment; sedimentary geochemistry; measurement of metals; origin; tectonic location